Visual Communication Is Becoming Multidimensional in A Changing Socio-Economy Impacted by Science and Technology - Jadhav, Nilima Suhas; Dhobley, Milind (Journal of Neonatal Surgery, 2025)
The landscape of visual communication is undergoing a significant transformation, influenced by rapid scientific and technological progress alongside dynamic socioeconomic shifts. Innovative digital tools, Artificial intelligence, immersive technologies like virtual and augmented reality, and the metaverse are reshaping how information is shared and interpreted. This evolving multidimensional approach enhances user engagement, accessibility, and interaction with the help of the explorative method, redefining communication in an increasingly interconnected society. As these advancements continue, visual communication remains integral to shaping perceptions, influencing behaviours, and crafting cultural narratives.